Sustainably reducing device utilization and device-related infections with DeCATHlons, device alternatives, and decision support. (30th November 2020) - Lesho, Emil P.; Clifford, Robert; Vore, Kelly; Zsenits, Balazs; Alcantara, Jose; Gargano, Bryan; Phillips, Matthew; Boyd, Susan; Eckert-Davis, Laura; Sosa, Carlos; Vargas, Roberto; Riedy, Dawn; et al.
Abstract: Engagement of frontline staff, along with senior leadership, in competition-style healthcare-associated infection reduction efforts, combined with electronic clinical decision support tools, appeared to reduce antibiotic regimen initiations for urinary tract infections ( P = .01). Mean monthly standardized infection and device utilization ratios also decreased ( P < .003 and P < .0001, respectively).